Synthesis of C-10 Tabersonine Analogues by Palladium-Catalyzed Cross-Coupling Reactions - Chen, Fanglei; Lei, Min; Hu, Lihong (Synthesis, 2014)
A series of C-10-substituted tabersonine analogues have been synthesized via palladium-catalyzed cross-coupling reactions. To be specific, tabersonine reacted with NIS in TFA to generate the 10-iodotabersonine, which participated in palladium-catalyzed or palladium/copper co-catalyzed cross-coupling reactions, such as Suzuki–Miyaura cross-coupling reaction, Heck reaction, and Sonogashira cross-coupling reaction, to afford C-10 tabersonine analogues. These protocols provide the possibility of introducing substituents with structural diversity and complexity into the C-10 of tabersonine for the pharmacological activity screening.
Keywords: tabersonine; palladium catalysis; Suzuki–Miyaura cross-coupling reaction; Heck reaction; Sonogashira cross-coupling reaction